USING METHODS OF FORMING SOCIAL CONSCIOUSNESS IN MORAL EDUCATION OF STUDENTS - Feruza Aminovna Turakulova; Raimov Jasur Jakhongirovich (Galaxy International Interdisciplinary Research Journal, 2022)
Moral education is the main direction of the general system of comprehensive development of a person; the process of purposeful initiation of children into the moral values ​​of humanity and a certain society; moral qualities, character features, formation of skills and behavioral habits. Educating students from a moral point of view is the basis of all human actions. It shapes the appearance of his personality, determines his value system, the features of the process of forming the student's personality. In this regard, purposeful use of the methods of formation of moral consciousness is one of the most important tasks of forming the student's personality to learn moral standards and requirements.